Making the selectable marker bar tighter and more economical - S Hays; E U Selker (Fungal Genetics Reports, 2000)
Use of the bacterial basta resistance gene (bar) as a selectable marker in Neurospora was reported by Avalos et al (1989 Curr. Genet. 16:369-372).